If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 4x + 2(-5 + 26) = 4 Combine like terms: -5 + 26 = 21 4x + 2(21) = 4 Multiply 2 * 21 4x + 42 = 4 Reorder the terms: 42 + 4x = 4 Solving 42 + 4x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + 4x = 4 + -42 Combine like terms: 42 + -42 = 0 0 + 4x = 4 + -42 4x = 4 + -42 Combine like terms: 4 + -42 = -38 4x = -38 Divide each side by '4'. x = -9.5 Simplifying x = -9.5

| B=rt+r | | 3(2x+1)=18x | | 5(9.5)+y=26 | | 4x+22=26 | | 5(4-2y)=26 | | 3x=x-20 | | 4x-2(6)=4 | | d^2+10d+24=0 | | p^2+18p+81=0 | | a^2-9a+20=0 | | m^2+m-56=0 | | 5n^2+26n+5=0 | | 2k^2-13k+11=0 | | 3p^2-19+28=0 | | 6x^3+12x^2-38x+12= | | 6x^3+13x^2-38x+12= | | 7y-8=13 | | x^2+169=0 | | 8a-10+a+2-4a=17 | | 8a-10+a+2-4a=16 | | 5x+7-8x+6x=13 | | -55-4=5-10x | | -55-4x=5-10x | | 200-6x=6x+20 | | 4x-6=-2 | | 3t+4=t+14 | | 6x+7=4x+12 | | 10x+5y=13 | | -3-5x+20+2x=5 | | 1+12x=16x-55 | | -23-4x=10x+22 | | 3x^2-41x+26=0 | | 38X^2+3X-45= | | 14-10x=62-24 | | 14-10x=62-24x | | 2x-3=78-7x | | 3(x-6)=54-5x | | 9(x+2)=3(x+22) | | 55+60*2-34+88*0+55-62+-65*0+2= | | y=(2a-6)a+3 | | mx^2-3mx+3=0 | | px^2+2(p+2)x+p+7=0 | | n=(2n-3)/5 | | x^4-6x^3-7x^2+36x+36=0 | | 3x^2-15x-23=0 | | 2x-5y=-5 | | 2(x-1)=3x+4 | | 8x+11=3x+21 | | 3x^3+7x^2+10x+27=0 | | 7x^2+10x+27=0 | | 3(x-2)=4(3-x) | | 6x-7=x-27 | | 3-10b=26-9 | | 4y-8=36 | | x^6-x-0.2=0 | | -3x+1=16 | | a-15+2a=45 | | 5i-127=-127+5i | | 5.4y+5.31=-4.41 | | -3.2+0.7p=0.9p+5.1 | | -6x^2-4x+6=0 | | 10-3x=-2x | | 2x=b-4a | | 2x=b-5a | | 9-2d=d-3 |